Central Heating Policy and Population Migration in China: An Empirical Study - Gao, Yannan; Sampattavanija, San (International Journal of Energy Economics and Policy, 2023)
The Huai River policy divides the country into the areas with and without central heating. This paper first determines the location of the south-north central heating borderline in China based on the Huai River policy, and then studies the differences in population migration between the north and the south. It proposes three factors that influence people’s decision to migrate through district heating: heating costs, indoor living conditions, and outdoor air quality. Through the analysis of the county-level data in China, the following three basic conclusions are drawn: first, based on the estimation of the total sample, the total effect of central heating on population in-migration is negative; Second, central heating positively impacts in-migration in wealthier counties, while the impact is negative in less-developed counties. Third, the heating boundary policy affects population migration via air pollution. However, air pollution is not the decisive factor.